e-CALF (Electronic Version of Contextual Attractive Logical Fun) Game as Self-Directed Learning Media for Students in the Digital Era - Mahayanti, Ni Wayan Surya; G.A.P., Suprianti; Utami, I.A.M.I.; Kusuma, I.P.I. (JPI (Jurnal Pendidikan Indonesia), 2019)
The study aimed at developing a prototype digital game e-CALF (electronic version of Contextual Attractive Logical and Fun) as self-directed learning media for elementary school students. The research was conducted in SD Lab Singaraja in which the subjects of the study were one class representative in each grade of the students. The design of this research was adapted from ADDIE Model. The data was gained by using interview guide, observation sheet, questionnaire and expert judgment rubric. Since it was found that almost 90% of students in SD Lab Undiksha have their own smartphone, it is a need to design digital media which can facilitate them doing self-directed learning at home. As the result, e-CALF is designed, developed, and revised and at the end of this study, the e-CALF can be categorized as an excellent media. The score of the material given by the first, second, and third judges are 110, 110.5, and 111. Those scores are in a range of X â‰¥ 103.5 which is categorized as an excellent content. From media expert, the accumulation score gained is 148. The score is in a range of X â‰¥ 139.5 which is also categorized as an excellent media.